2019
DOI: 10.14245/ns.1836320.160
|View full text |Cite
|
Sign up to set email alerts
|

Step-by-Step Sublaminar Approach With a Newly-Designed Spinal Endoscope for Unilateral-Approach Bilateral Decompression in Spinal Stenosis

Abstract: Objective Spinal stenosis is increasingly common due to population aging. In elderly patients with lumbar central canal stenosis (LCCS), minimizing muscle damage and bone resection is particularly important. We performed a step-by-step operation with a newly designed spinal endoscope to obtain adequate decompression in patients with spinal stenosis. Methods From April 2015 to August 2016, 78 patients (48 males, 30 females) with LCCS (91 segments) underwent endoscopic de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 17 publications
3
33
0
Order By: Relevance
“…However, these complications can be potentially avoided with various endoscopic spinal procedures that can be done under local anaesthesia and epidural anaesthesia, which allow for early postoperative recovery and mobility without a significant effect on the central nervous system. [32][33][34][35][36]…”
Section: In Sickness: the Role Of Endoscopic Spine Surgery In Patientmentioning
confidence: 99%
“…However, these complications can be potentially avoided with various endoscopic spinal procedures that can be done under local anaesthesia and epidural anaesthesia, which allow for early postoperative recovery and mobility without a significant effect on the central nervous system. [32][33][34][35][36]…”
Section: In Sickness: the Role Of Endoscopic Spine Surgery In Patientmentioning
confidence: 99%
“…[8][9][10] The outside-in technique of decompression is what is described as over the top decompression in minimally invasive literature for both microscopic and endoscopic surgery. [11][12][13] The authors defined outsidein technique of endoscopic stenotic decompression as bony decompression of cephalad lamina, caudal lamina, inferior articular process, and superior articular process ("outside") to the extent that is sufficient for complete release of ligamentum flavum prior to removal of ligamentum en bloc with blunt instrument in the last part of the procedure to expose the spinal canal ("in"). The inside-out technique, on the other hand, involved bony decompression of lamina, inferior articular process, and superior articular process with early splitting of ligamentum flavum to get into spinal canal ("inside") prior to releasing ligamentum flavum from within the spinal canal with concurrent bony decompression ("out").…”
Section: Introductionmentioning
confidence: 99%
“…Ito et al demonstrated improved VAS, ODI and Japanese Orthopedic Association (JOA) score after conducting endoscopic decompression with sublaminar approach. [24] Kang et al compared biportal endoscopic surgery with microscopic surgery and found that there was shorter hospital stay, shorter operation time, less hemovac drainage and less opioid use in endoscopic surgery group. [25] Kim and Choi found satisfactory results at minimum 2-year follow-up with no wound infection or segmental spinal instability after conducting endoscopic decompression for lumbar spinal stenosis.…”
Section: Discussionmentioning
confidence: 99%